THE ROLE OF LECTURING IN THE SCIENCE OF INFORMATION AND COMMUNICATION TECHNOLOGIES AND SYSTEMS IN THE ECONOMY - Nematulla Abdukarimovich Gulbayev; Nafosat Nozimovna Raimjanova (Web of Journals Publishing, 2024)
The role of lecture preparation during classes is generalized based on the authors' many years of experience using the example of the science of information and communication technologies and systems in economics.
Keywords: information, lecture, communication, system, lesson, subject.